IL-10 producing regulatory and helper T-cells in systemic lupus erythematosus. (August 2019) - Geginat, J.; Vasco, M.; Gerosa, M.; Tas, S.W.; Pagani, M.; Grassi, F.; Flavell, R.A.; Meroni, Pl.; Abrignani, S.
Highlights: IL-10 has a dual role in immune responses. IL-10 is increased in lupus, promotes autoantibody production and is evaluated as a therapeutic target in SLE patients. IL-10 producing subsets of regulatory T-cells and B helper T-cells play different roles in B-cell responses and in lupus. Abstract: Systemic lupus erythematosus (SLE) is a highly heterogeneous autoimmune disease characterised by the production of pathogenic autoantibodies against nuclear self-antigens. The anti-inflammatory and tolerogenic cytokine Interleukin-10 appears to play a paradoxical pathogenic role in SLE and is therefore currently therapeutically targeted in clinical trials. It is generally assumed that the pathogenic effect of IL-10 in SLE is due to its growth and differentiation factor activity on autoreactive B-cells, but effects on other cells might also play a role. To date, a unique cellular source of pathogenic IL-10 in SLE has not been identified. In this review, we focus on the contribution of different CD4 + T-cell subsets to IL-10 and autoantibody production in SLE. In particular, we discuss that IL-10 produced by different subsets of adaptive regulatory T-cells, follicular helper T-cells and extra-follicular B-helper T-cells is likely to have different effects on autoreactive B-cell responses. A better understanding of the role of IL-10 in B-cell responses and lupus would allow to identify the most promising therapies for individual SLE patients in the future.